Chapter 4 How Memory Comes to Matter From Social Media to the Internet of Things - Giaccardi, Elisa (Routledge Research in Cultural and Media Studies, 2017)
Memory matters. It matters because memory brings the past into the present, and opens it up to the future. But it also matters literally, because memory is mediated materially. Materiality is the stuff of memory. Meaningful objects that we love (or hate) function not only as aide-mémoire but are integral to memory. Drawing on previous scholarship on the interrelation of memory and materiality, this book applies recent theories of new materialism to explore the material dimension of memory in art and popular culture. The book's underlying premise is twofold: on the one hand, memory is performed, mediated, and stored through the material world that surrounds us; on the other hand, inanimate objects and things also have agency on their own, which affects practices of memory, as well as forgetting. Chapter 1 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138203235_oachapter1.pdf Chapter 4 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138203235_oachapter4.pdf Chapter 5 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138203235_oachapter5.pdf